2019
DOI: 10.1108/nfs-08-2019-0263
|View full text |Cite
|
Sign up to set email alerts
|

Herbal infusions and health

Abstract: Purpose Increasingly, interest in and the uptake of herbal infusions has advanced, namely, owing to their bioactive properties and potential links to health. Given this, the purpose of the present review was to collate evidence from human trials for five popular herbal infusions. Design/methodology/approach The systematic review comprised ten human trials (560 participants), investigating inter-relationships between herbal infusions consumption and health. Only human studies involving German chamomile (Matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Although this experimental design is weaker than a randomized controlled trial with respect to establishing a cause-effect relationship, before-and-after approaches have been widely used. [50][51][52][53][54] Moreover, the present single-group beforeafter design could be biased by the modification of the subjects' lifestyle (Hawthorne effect). According to previous studies protocols, [55][56][57][58][59] participants were instructed not to modify their dietary and physical habits.…”
Section: Discussionmentioning
confidence: 99%
“…Although this experimental design is weaker than a randomized controlled trial with respect to establishing a cause-effect relationship, before-and-after approaches have been widely used. [50][51][52][53][54] Moreover, the present single-group beforeafter design could be biased by the modification of the subjects' lifestyle (Hawthorne effect). According to previous studies protocols, [55][56][57][58][59] participants were instructed not to modify their dietary and physical habits.…”
Section: Discussionmentioning
confidence: 99%
“…There are around 3 billion people who enjoy drinking tea and infusions globally with this seen as an inexpensive complementary alternative medicine [27]. It has been previously reported that tea and herbal infusions are a valuable source of flavonoids and other polyphenols and that ingestion (around 1 to 3 cups daily) could potentially benefit certain aspects of health [28]. In particular, L-theanine, an amino acid naturally found in green and black tea (Camellia sinensis) is thought to help attenuate the negative effects of psychological stress and anxiety on health [29].…”
Section: Resultsmentioning
confidence: 99%
“…Mixture of herbal infusions have high anti-oxidant activities that could play a role in the management of health conditions such as diabetes (Etheridge and Derbyshire, 2019). WUB was tested by liquid chromatography-mass spectrometry (LC-MS) to identify phenolic compounds qualitatively with positive ionization mode.…”
Section: Resultsmentioning
confidence: 99%